A morphological phylogeny of Agrotis Ochsenheimer (Lepidoptera, Noctuidae), with emphasis on the South American species. (2nd December 2014) - San Blas, Germán
<x xml:space="preserve">Abstract</x> The monophyly of Agrotis Ochsenheimer in addition to the relationships among the South American species of the genus and the relationship between Agrotis and Feltia Walker are examined. A cladistic analysis was performed based on 45 terminals, with 28 ingroup and 17 outgroup taxa, and 126 characters (two continuous and 124 discrete) from adult morphology, including male and female genitalia. Parsimony analyses were performed under equal and implied weighting. Results support Agrotis as a monophyletic group, sister to the South American species of Feltia (Feltia tent.), and the latter being more closely related to Agrotis than to the 'true' Feltia. Species of Agrotis that branched off first (including the type species) have characters shared with both Feltia and Agrotis. South American species of Agrotis (with some proviso) form a clade that branched off later, with some weakly supported species groups that had been proposed in previous works. Biogeographical aspects of the group are discussed after optimizing species distributions on the tree. Trees obtained after analyses using implied weights show similar relationships to those under equal weights, particularly regarding Feltia tent., showing Feltia tent. plus Agrotis forming a monophyletic group, sister to the 'true' Feltia.